Metal–Semiconductor Phase‐Transition in WSe2(1‐x)Te2x Monolayer. Issue 4 (22nd November 2016) - Yu, Peng; Lin, Junhao; Sun, Linfeng; Le, Quang Luan; Yu, Xuechao; Gao, Guanhui; Hsu, Chuang‐Han; Wu, Di; Chang, Tay‐Rong; Zeng, Qingsheng; Liu, Fucai; Wang, Qi Jie; et al.
Abstract : A metal‐semiconductor phase transition in a ternary transition metal dichalcogenide (TMD) monolayer is achieved by alloying Te into WSe2 (WSe2(1− x ) Te2 x, where x = 0%–100%). The optical bandgaps of the WSe2(1− x ) Te2x monolayer can be tuned from 1.67 to 1.44 eV (2H semiconductor) and drops to 0 eV (1Td metal), which opens up an exciting opportunity in functional electronic/optoelectronic devices.